The Role of Law in Engineering “Natural” Disasters - MacEvoy, Arthur F. (Oñati Socio-Legal Series, 2013)
What people perceive as “natural disasters” typically take place when extractive industries operate at levels high enough that the ecological systems from which they draw resources lose their ability to buffer transient shocks, whether of environmental or technological origin. Legal institutions whose purpose it is to prevent such disasters from taking place may in fact encourage them, insofar as they must also broker competing demands for greater access to resources. Legal institutions may adapt to ecological instability in the wake of such disasters, “learning” from the experience more or less successfully depending on the conditions under which the disaster takes place. This paper will develop these ideas in the context of a number of noteworthy disasters, including the sinking of the Deepwater Horizon in 2010.